2016
DOI: 10.1016/j.ejpb.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Mucus permeating thiolated self-emulsifying drug delivery systems

Abstract: Low molecular weight thiol-conjugates were identified to improve the mucus permeation, leading to highly efficient mucus permeating SEDDS, which were superior to conventional SEDDS and might thus be a new carrier for lipophilic drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 34 publications
1
30
0
1
Order By: Relevance
“…Several studies have investigated mucus diffusion of hydrophobic compounds Rohrer et al, 2016). In fact, the permeation of hydrophobic molecules was blocked in mucus network by interaction with hydrophobic domains of mucus.…”
Section: Mucus Diffusion Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated mucus diffusion of hydrophobic compounds Rohrer et al, 2016). In fact, the permeation of hydrophobic molecules was blocked in mucus network by interaction with hydrophobic domains of mucus.…”
Section: Mucus Diffusion Studiesmentioning
confidence: 99%
“…SEDDS composed of oil, surfactants and cosurfactants that are spontaneously emulsified in gastric fluid are not only used to incorporate poor water-soluble drugs but their protection against enzymatic degradation is also shown (Friedl et al, 2013;Rohrer et al, 2016;Zupančič et al, 2016). In addition, SEDDS can rapidly diffuse through mucus due to their small average droplet size and their shape deformation ability and exhibit high affinity to phospholipid bilayer of intestinal cells.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally in this study, these thiolated NPs did not alter human nasal ciliary beat frequency (CBF) in vitro , which suggests that these NPs are not toxic and did not adversely impact the function of mucociliary clearance. Thiol-conjugates were also incorporated into SNEDDS, leading to an average droplet size of 50 nm and neutral charges (Rohrer et al, 2016). In this study, those systems were used in vitro for permeation studies in pig intestinal mucus using multiple particle tracking (MPT) technique, demonstrating a 66-fold increase in diffusion coefficient when compared to unthiolated control.…”
Section: Transmucosal Drug Deliverymentioning
confidence: 99%
“…Utilizing this approach, it was reported that drug delivery systems which featured thiol groups on their surface can interacted with cysteine rich domains of mucin via thiol‐disulfide exchange reaction and effectively increase the permeation properties through the mucus . For example, Wang et al conjugated cysteine to PAA and investigated the presence of the thiol function in the context of an mucus permeation enhancer.…”
Section: Mucus Penetrationmentioning
confidence: 99%
“…For example, Wang et al conjugated cysteine to PAA and investigated the presence of the thiol function in the context of an mucus permeation enhancer. [108b] It was shown that the permeability through rat intestinal mucosa were dependent on both, the molecular weight and the amount of cysteine conjugated to PAA. At a constant degree of thiolation, the permeation properties increased with increasing molecular weight from 100 to 450 kDa.…”
Section: Mucus Penetrationmentioning
confidence: 99%